SCIENTIFIC PRODUCTION ON PSYCHOLOGY IN MOZAMBIQUE: BIBLIOMETRIC ANALYSIS IN THE WEB OF SCIENCE AND SCOPUS BASES. - Balsan, Laércio André Gassen (2024)
Currently in Mozambique there is a significant volume of publications and scientific events in Psychology, something positive given its importance for the development of the field. This study aimed to describe the characteristics of national scientific production on Psychology between 2003 and 2023. The study is bibliographic, exploratory in nature and quantitative approach through bibliometric analysis, focusing on 61 publications indexed in the Web of Science (WOS) and Scopus databases, covering all areas of Psychology in the country. The criteria were: bibliographic survey process, number of publications per year, typology of publications, the journals that published the most and their impact factor, main areas researched, authors who published the most and most cited, and their institutional affiliations. Revealed that the national scientific production on Psychology is growing over time, and that 2020 was the year that registered the most publications. They also revealed a higher concentration of publications in the area of multidisciplinary psychology, and that most of the publications are scientific articles, highlighting those of Germano VC, and the Eduardo Mondlane University as the national institution that produces the most on the subject.